'It's Different Now': A Narrative Analysis of Recent Irish Migrants Making Sense of Migration and Comparing Themselves with Previous Waves of Migrants. Issue 2 (November 2015) - Ryan, Louise
The key aim of this paper is to consider how young professionals, who left Ireland since the economic recession, define their migration project – not just individually but also as a shared experience across their generation. Using narrative analysis and the concept of 'speech acts', I explore how these young people working in England talk about and make sense of recent Irish migration. In particular, the paper explores the extent to which the participants construct a sense of 'cohorts' to articulate their shared experiences and expectations as a 'group', 'wave' or 'generation' of recent migrants and, in so doing, contrast themselves with previous waves of migrants from Ireland. I highlight their emphasis on 'choice', 'opportunities' and 'mobility' in contrast to their image of the older Irish migrants as 'forced', disadvantaged and 'stuck'. I suggest that this is not just an over-simplification of the past, but more importantly represents a device for making sense of the present. The paper also adopts a reflexive approach and situates myself as a researcher and an Irish migrant in the research process. In this way, I consider how my questions and comments may have influenced how narratives were constructed and shared as well as how I may have approached the analysis of the data through a specific socio-temporal mind set.